Navigating Workplace Morality: Unveiling Trends in Counterproductive Work Behavior - Ibrahim, Nor Hafizah; Makhbul, Zafir Khan Mohamed; Ayob, Abu Hanifah; Lokman, Anitawati Mohd (SCAD Independent, 2025)
Counterproductive work behavior (CWB) involves unethical conduct with detrimental effects on organizations and their members, resulting in diminished productivity and job satisfaction. This study is crucial for understanding CWB, to provide a comprehensive understanding of the global landscape of CWB research that might guide future research and practical interventions in this area. Examining 955 CWB publications from Scopus spanning 1999 to 2023, the study employed a comprehensive bibliometric analysis using Publish or Perish, VOSviewer, and Excel. In addition to identifying the current landscape, prominent publication sources, and influential articles, the analysis uncovered significant themes, such as demographics, emotional and psychological factors, and job-related characteristics, among others, highlighting a notable interest among researchers in comprehending the various aspects and consequences of CWB. The bibliometric evaluation provided valuable insights, emphasizing collaboration, replication, and knowledge expansion for future research. The article concluded with a discussion of the implications and limitations of the findings.